UPAYA GURU WALI KELAS DALAM PEMBENTUKAN PERILAKU SISWA BARU DI PONDOK PESANTREN MIFTAHUL HUDA AL WUSTHO BOYOLALI TAHUN AJARAN 2023/2024 - Azzahroh, Fatimah; Suhadi, Suhadi; Ulfah, Yetty Faridatul (UMSU, 2024)
The aim of this research is 1) To find out what efforts teachers make to shape the behavior of new students at the Miftahul Huda Al Wustho Boyolali Islamic boarding school for the 2023/2024 academic year. 2) To find out the obstacles in shaping the behavior of new students at the Miftahul Huda Al Wustho Boyolali Islamic boarding school for the 2023/2024 academic year. In this research the researcher used a qualitative approach with a descriptive approach. The setting for this research was carried out at the Miftahul Huda Al Wustho Boyolali Islamic boarding school. The researcher's data collection technique used three research methods, namely interviews, observation and documentation. The result and conclusion of this research are the homeroom teacher's efforts in shaping student behavior. It can be concluded that the homeroom teacher's efforts in shaping student character include: good school principal management. Teachers set examples for students so that students see and imitate them. Implement learning programs with adequate facilities so that students do not get bored. Carrying out worship activities such as dhikr, memorization and prayer. Always carry out evaluations of activities during learning so that existing problems can be immediately resolved. Factors that hinder teachers' efforts to shape student behavior are bad student behavior, parents who are indifferent to their children's conditions and student environmental factors. Apart from that, there are also supporting factors, so that these obstacles can be resolved, including teachers working together and adequate learning facilities.